Analisis Determinan Kualitas Audit Internal Sektor Publik di Indonesia: Systematic Literature Review - Rajafi, Lalu Roby; Irianto, Gugus; Baridwan, Zaki (STIE Malangkucecwara, 2024)
The objective of this research is to analyze factors that influence the internal audit quality of Indonesia’s public sector by systematically reviewing empirical literatures published from 2019 to 2024. The data collection and classification was conducted on Google Scholar and Scopus databases using PRISMA, resulting in 39 studies to be used as the sample. The Systematic Literature Review (SLR) analysis suggests 19 variables that influence the internal audit quality of Indonesia’s public sector; fifteen of which (79%) have positive impacts on the internal audit quality, while the remaining four (21%) have negative effects. The factors that positively influence the public sector’s internal audit quality are auditor’s competence, independency, professionalism, experience, ethics, motivation, integrity, accountability, performance, objectivity, self-efficacy, and capability, management support, audit supervision, and internal control. Meanwhile, factors that negatively influence the audit quality are time pressure, work load, supervisor’s order, and obedience pressure.